ADVERBIA DALAM BAHASA ARAB DAN BAHASA INGGRISÂ Analisis Kontrastif - , MOCHAMAD CHODERIN, Dr. Amir Maâruf, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis is a study related to the system adverbs in Arabic and English with a contrastive analysis approach. Contrastive analysis approach was used to assess differences and similarities, especially in the syntactic structure of adverbs in Arabic and English at the unit level of words, phrases, clauses in a sentence. In collecting the data, the researcher uses observation method and recording technique. The English adverbs are collected from the English grammar books